Beyond Rape: Dacia Maraini's Donna in guerra and Maria Schiavo's Macellum in the 1970s Italian Feminist Debate on Gender Violence. (2nd October 2017) - Mandolini, Nicoletta
Abstract: This article reads two feminist literary works on gender violence, Maraini's Donna in guerra (1975) and Schiavo's Macellum (1979), through the lens of the political discourse that the Italian feminist movement developed in relation to the issue of rape in the late 1970s. Adopting the classification offered by Johan Galtung's theory on direct, structural and cultural violence, as well as Pierre Bourdieu's theorization on symbolic violence, this essay aims at pinpointing ideological differences between Maraini's and Schiavo's narratives. In particular, it argues that, if Donna in guerra denounces direct and structural abuses on women, thus calling for institutional change, Macellum is an accusation against a cultural violence that cannot be fought with the tool of law. Maraini's and Schiavo's approaches, which mirror the standpoints of different factions of the movement of the time, are then considered in relation to Teresa de Lauretis' ideas on the structure of feminist thought and politics, in order to illustrate that both approaches are in fact essential for the subversion of violent sexist dynamics.